Eye movements are stable predictors of word reading ability in young readers - Strandberg, Andrea; Nilsson, Mattias; Östberg, Per; Seimyr, Gustaf Öqvist (Frontiers in Education, 2023)
During the first years of formal instruction in reading, there are developmental changes to the characteristics of children’s eye movements that correspond to their progress. Generally, these changes are driven by improved text processing and a shift from reliance on sub-lexical to lexical processes. Currently, however, little is known about to what extent early eye movements during reading accounts for variations in later word reading ability. In this paper we investigate this association in an ecological context involving 164 children in first grade and 206 children in second grade. We recorded their eye movements during normal text reading and analyzed to what extent they account for variation in word reading ability one year post-recording, and make comparisons to concurrent predictions. Regression analysis revealed that eye movements accounted for approximately 60 % of the variance in concurrent word reading ability and approximately 48 % one year later. Mean fixation duration explained unique variance in reading ability and largely drives the correlation. Proportion of regressions was not a significant longitudinal predictor among the youngest readers. The difference between the concurrent and longitudinal predictions was greatest in the younger children, which was in line with our expectation. Findings are discussed in relation to current models of word reading. Our results suggest that eye movements are stable predictors of word reading ability. Ultimately, knowledge of what can be gleaned from early readers’ eye movements about later word reading ability could help inform assessments of reading development in the educational setting, where the presence of digital assessment tools is growing.